Kramer Williamson, Sprint car legend - Culver, Chad (McFarland & Company, Inc., Publishers, 2017)
"Sprint Car Hall of Famer Kramer Williamson began his 45-year professional career as grassroots racer and became one of the most successful professional drivers of all time. Drawing on interviews, this biography covers his life and career, from his beginnings racing the #73 Pink Panther car in 1968 to his fatal crash at Lincoln Speedway in 2013"--